The strategies used by post-graduate students to avoid plagiarism in thesis writing - Eka Putri Andayani; Siti Sarah Fitriani; Dohra Fitrisia (Universitas Syiah Kuala, 2021)
This study aims to find out the perception of post-graduate students on plagiarism, the influenced factors, and the strategies used by the students to avoid plagiarism in thesis writing. To collect the data, 10 post-graduate students of Graduate Study of English Education at University of Syiah Kuala (USK) were chosen randomly based on the predetermined criteria: the students in the academic year 2016 and 2017 who have written their thesis. The data were collected through interviews. The result of data analysis shows that the post-graduate students of English Education at USK have the same perception about the issue of plagiarism in thesis writing. The factors contributing to plagiarism are limited time, the deadline, technological development and ease of accessing online sources, students' laziness, lack of understanding to paraphrase, and poor understanding of plagiarism. Furthermore, two main strategies can be used to avoid plagiarism in thesis writing. The first is paraphrasing and quoting other peoples' ideas. The second is reading a lot of sources from many articles and journals to learn how the authors develop their idea in their writing and how to put citations and references appropriately.